1997
DOI: 10.1515/znc-1997-9-1017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Scopoletin and Aflatoxin Bj on Bovine Hepatic Mitochondrial Respiration in vitro

Abstract: A comparative study of the in vitro effects of the coumarin compounds, scopoletin and aflatoxin B1 (AFB1), on bovine (Bos indicus) hepatic mitochondrial respiration was carried out polarographically, using isocitrate -NAD+ (3 - site), succinate (2- site), and reduced cytochrome c (1 - site), as respiratory substrates. Both scopoletin and AFB1 elicited a substrate - dependent stimulation or inhibition of the mitochondrial states 4 and 3 respiration. The results suggest that AFB1 has a higher tendency to inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In our previous studies, we showed that both AFBj and scopoletin interfered with bovine he patic mitchondrial respiration in vitro (Obasi and Obidoa, 1997a). Interference with mitochondrial respiration could imply that the compounds in teracted with a num ber of the enzymatic processes of respiration, particularly the respiratory com plexes.…”
Section: Introductionmentioning
confidence: 93%
“…In our previous studies, we showed that both AFBj and scopoletin interfered with bovine he patic mitchondrial respiration in vitro (Obasi and Obidoa, 1997a). Interference with mitochondrial respiration could imply that the compounds in teracted with a num ber of the enzymatic processes of respiration, particularly the respiratory com plexes.…”
Section: Introductionmentioning
confidence: 93%